Educating the countryside: The familiar agricultural extension in Portugal - Borges, P. N.; Freire, D. (Rural History 2023, 2023)
During the 20th century, extension services proved particularly important in public policies to modernize agriculture. Historiography has shown how experts from the United States of America influenced the design and implementation of extension programme in European countries and on other continents, especially during the green revolution. Starting from the Portuguese case, this paper aims to analyse how these extension ideas and practices were adapted to the political, economic and social specificities of the country during the Estado Novo dictatorship (1933-1974). In fact, during the Estado Novo dictatorial regime several initiatives were organised and disseminated in rural areas, such as professional agricultural training courses that began in 1936 promoted by technicians from the General Directorate of Agricultural Services of the Ministry of Agriculture. From 1957 onwards, some courses were particularly aimed at rural families. It seems that the initiatives sought to complement the technical courses with classes in home economics, assuming itself as the service of Family Agricultural Extension. If technological innovation was an objective in the fields, the same social change should occur at home. The courses were given to rural young people of both genders, but apparently with a particular focus on girls, with classes in cooking, sewing, childcare, cleaning, and other domestic tasks and ideals of civility and community life. This paper is a presentation of the preliminary results of an ongoing investigation of the Familiar Agricultural Extension in Portugal, connecting these initiatives with what was taking place in other European countries.